An In Vitro evaluation of biodegradability of stainless steel crowns at various salivary pH - K Anusha; E Sridevi; A J Sai Sankar; M Sridhar; K Siva Sankar; K Harish Chowdary (Wolters Kluwer Medknow Publications, 2020)
Aim: To evaluate the biodegradability of preformed stainless steel crowns at varying salivary pH and the cytotoxic effect of leached out elements on fibroblasts. Methodology: A total of 243 stainless steel crowns were selected and were divided into 3 groups (I, II, III) based on Ph of immersion media. The pH of samples in group I, II, III were 4.3, 5.5 and 6.3 with 81 crowns in each group. Each group has 9 samples with 8 crowns in each sample. All samples were immersed in polyethylene bottles containing 10ml of artificial saliva and incubated at 37°C for 4 weeks. All the samples were analyzed on 1,7,14 and 21 days by atomic absorption spectrophotometer for the quantitative assement of Ni, Cr and Fe. Fibroblast tissue culture was used to assess the cytotoxicity of the samples. Statistical Analysis: Analysis of variance. Results: Maximum release of Ni, Cr, Fe ions were observed at pH 4.3 followed by pH 5.5 and least release of ions were observed at pH 6.3 from SS crowns. The cytotoxic results showed that the least cell viability of cells was seen at pH 4.3. Conclusion: With decrease in pH, there is an increase in ion release from stainless steel crowns and the mean release of nickel, chromium and iron were very much below the average dietary intake. But the allergic manifestations of ions like nickel can't be ruled out.